Developmental Crime Prevention in the Twenty-first Century: Generating Better Evidence Embedded in Large-scale Delivery Systems - Homel, Ross (Journal of developmental and life-course criminology, 2021)
In recent decades, a strong foundation for developmental crime prevention has been constructed by a small band of criminologists, including the authors in this special issue. However, the evidence base is incomplete and needs strengthening. Moreover, the “flagship programs” that largely constitute the evidence base simply establish “proof of concept” rather than providing evidence readily translatable into policies for sustainable, population-wide crime prevention. I propose the development of a research agenda for both type 1 translation (applying basic scientific research to the development and testing of new prevention initiatives) and type 2 translation (investigating the complex processes and systems through which evidence-based practices are adopted, implemented, and sustained on a large scale). The agenda could include (a) experiments that integrate universal, selective, and indicated interventions; (b) study of the crime prevention effects of “services as usual” because routine services can be the pathway to scale; (c) research in partnership with practitioners and communities to construct risk and protective factor profiles to guide prevention planning, implementation, and evaluation; (d) type 1 research in areas where better evidence is needed; and (e) better integrating the timing of interventions with knowledge about the development of criminal propensity. I argue that type 2 translation could be viewed as the new frontier for developmental crime prevention, requiring a shift in focus from programs to systems and new research methodologies such as those developed in the CREATE Project, which has built electronic and human infrastructure to help bridge the gap between developmental prevention research and routine services.